2013
DOI: 10.1177/1091581812472209
|View full text |Cite
|
Sign up to set email alerts
|

Uterotrophic Assay of Percutaneous Lavender Oil in Immature Female Rats

Abstract: The estrogenic potential of lavender oil was evaluated in a percutaneous uterotrophic bioassay in immature female rats. Four groups of 10 immature female rats each were randomly selected on postpartum day (PPD) 16. During the 3-day treatment period (PPDs 19-21), the immature rats were separated from the dams, caged in groups of 5 in a litter box for 6 hours, and administered the vehicle control article (corn oil) or lavender oil at 20 or 100 mg/kg per day. All dosages were administered as a 5 mL/kg volume in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In one study, the comparative positive control used gavage of 17a ethynyl estradiol (44). The treatment schemes were quite different between the two groups, although it would have been a directly testable exposure with a fully accepted target end point if found positive (44). On the other hand, in our cases, the patients' suspected area of exposure, which was the breast area, was in direct contact with the essential oil and not at a distant site.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In one study, the comparative positive control used gavage of 17a ethynyl estradiol (44). The treatment schemes were quite different between the two groups, although it would have been a directly testable exposure with a fully accepted target end point if found positive (44). On the other hand, in our cases, the patients' suspected area of exposure, which was the breast area, was in direct contact with the essential oil and not at a distant site.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have demonstrated that dermal exposure to essential oils results in circulating concentrations that are comparable to the concentrations used in vitro (42,43). In contrast, an industry-supported experimental study reported percutaneous exposure of LO showed no uterotropic estrogenic activity (44). An additional report indicated no estrogenic activity in a yeast assay using Lin (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats with SI (90 mg/kg·d and 270 mg/kg·d) or E 2 (50 μ g/kg·d) administration show significant reduction in body weight. Uterine weight, used as a bioassay for estrogens [ 22 ], was measured after 4-week treatment ( Table 1 ). Uterus of lighter weight and lower concentration of E 2 were present after ovariectomy, which suggested that ovariectomy elicited estradiol deficiency and uterine atrophy ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous animal study reported that percutaneous injection of LO when performing uterotrophic assays on immature rats results in signi cantly reduced body weight gain after 3 days compared with that in the control group and a group administered 17α-ethinyl estradiol (19). However, the authors only assessed weight gain and organ-weight-to-terminal-body-weight to evaluate the presence of an estrogenic effect, and did not compared hormone levels or VO timing.…”
Section: Discussionmentioning
confidence: 99%